Pathophysiological aspects of sepsis and emergency management: A narrative review (Research, Society and Development, 2023)
Sepsis is classified as a medical emergency that describes the body's systemic immune response to a local inflammatory process, which can lead to organ dysfunction and death. Even though there is a great demand for updating medical management, the syndrome continues to be highly prevalent in Brazil and worldwide. This study is a narrative review with the purpose of discussing and describing sepsis and its pathophysiology, as well as demonstrating how this syndrome affects the personal lives of affected individuals. The following databases were used: SciElo (Scientific Electronic Library Online) and PubMed (US National Library of Medicine), with scientific data from January 10, 2023, with no language restriction and no restriction on the year of publication. Several studies show that sepsis is an alteration of the immune balance between inflammation and anti-inflammatory. Furthermore, the regulation of pro- and anti-inflammatory pathways in the face of sepsis leads to a non-local, but systemic release of cytokines, mediators and molecules related to pathogens, collaborating in the activation of coagulation and complement cascades. In short, sepsis remains a significant burden on healthcare systems around the world. However, the advances made in understanding its pathophysiology in the last 20 years surpass everything that has gone before.